El bestiario metafórico en "Doña Perfecta", de Galdós - Tarelli, Francisco (El Colegio de México, 2011)
The purpose of this essay is to refute the common notion that Galdós’s DoñaPerfecta is simply a “thesis novel” in favor of a broader and more complexview. The analysis of some dual-natured animal symbols (centaur, dragon,harpy, and basilisk) and their metaphorical function within the narrativecontext reveal an underlying structure characterized by ambiguity and duplicity,which means both a twofold quality and double-dealing. Duplicity is, inturn, strictly linked to the theme of the novel: deception and self-deception.